Patient blood management in elective bypass cardiac surgery: A 2-step single-centre interventional trial to analyse the impact of an educational programme and erythropoiesis stimulation on red blood cell transfusion - Hélène Charbonneau; Marie Pasquié; Pierre Berthoumieu; Nicolas Savy; Gérard Autones; Olivier Anglès; Anne Laure Berthelot; Madeleine Croute-Bayle; Isabelle Decramer; David Duterque; Yannick Gabiache; Valérie Julien; et al. (Contemporary Clinical Trials Communications, 2020)
Anaemia and iron deficiency are frequent in patients scheduled for cardiac surgery. Perioperative patient blood management (PBM) is widely recommended in current practice guidelines. The aim of this protocol is to analyse the effect of a global perioperative PBM programme on the red blood cell (RBC) transfusion ratio, morbidities and rehabilitation score in elective cardiac surgery.This study is a prospective, single-centre trial with a 2-step protocol, A and B, as follows: A: non-drug intervention: the caregiver is given a blood management educational programme; B: drug intervention: systematic correction of perioperative iron, vitamin deficiencies, and anaemia. This study was designed to enrol 900 patients (500 in group A and 400 in group B) in a rolling period starting at anaesthesia consultation and ending 3 months after surgery. The primary objective was a 20% reduction in RBC transfusion after implementation of PBM programmes (protocol A + B) when compared to our previous transfusion ratio in the first half of 2018 (30.4% vs 38%). The secondary objectives were to evaluate the impact for each step of the study on the RBC transfusion rate, morbidity and the quality of postoperative rehabilitation.The strength of this study is its evaluation of the effect of a global PBM programme on RBC transfusion in cardiac surgery through a 2-step protocol. We aim to assess for the first time the impact of non-drug and drug interventions on RBC transfusion, comorbidities and delayed rehabilitation parameters. Trials registrations: ClinicalTrials.gov, NCT04040023: registered 29 July 2019.